Marketing Strategy for Offshore Support Vessels (OSVs) in Indonesia - Laba, I Ketut; Simarmata, Juliater (Institut Transportasi dan Logistik Trisakti, 2024)
This research explores the marketing strategies and operational improvements of PT. Pertamina Trans Kontinental (PTK) in Indonesia's offshore support vessels industry using a qualitative method for in-depth analysis. The study focuses on product differentiation, flexible pricing, and digital marketing, demonstrating how these strategies enhance PTK's competitive edge. A SWOT analysis identifies PTK's strengths, weaknesses, opportunities, and threats, offering valuable insights for industry practitioners. However, the research is limited to PTK and the Indonesian offshore support vessels market, potentially not fully capturing the dynamics of non-captive markets or other regions. Future studies should expand the scope to include external variables and address the challenges of technology implementation and market changes, ensuring the long-term relevance of the findings.